Pills, pluralism, risk and citizenship: Theorising e-pharmacies - Brijnath, Bianca (2012)
This article uses the theoretical concepts of risk, imagination and pharmaceutical citizenship to understand the growing popularity of e-pharmacies and online health-seeking. I start with discussing how rapid social and economic forces such as globalisation, the rise of diasporic communities, increased use of technologies, changing notions of citizenship and risk, and the commodification of health have see the rise of e-pharmacies both licit and illegal. Then I explicate the links between the social imagination and pluralism; the relationship between e-pharmacies, risk and the state; and finally how the aim of achieving pharmaceutical citizenship prevails over national citizenship and the risks associated with using e-pharmacies. I conclude there are three ironies in this paradigm: (i) the common reasons for drug-purchasing among e-pharmacy consumers (associated as being technologised, high income earners) and drug consumers in low-income, poorly regulated societies; (ii) the irony of pluralism and hybridism-wherein drugs are marketed as exotic and unknown but embedded in scientific knowledge and credibility; and (iii) the irony of risk and the role of the state-wherein people prefer the unknown, that is, the risk of drugs bought online rather than the risks of the known, that is, the capacity of the state to actually and sufficiently care for its populace.